INVESTIGATION OF THE DRAWBACKS OF THE CURRENT NOTAM SYSTEM - Bogunenko, Mykola; Khomenok, Anastasiia (Proceedings of National Aviation University, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]-->The article deals with the analysis of the current NOTAM system, investigation of the factors that limit the NOTAM format, analysis of such drawbacks as human interpretation, information overload by the end use, geographical inaccuracy, not-self contained and hidden applicability<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->